Genome-wide SNP analyses reveal high gene flow and signatures of local adaptation among the scalloped spiny lobster (Panulirus homarus) along the Omani coastline - Al-Breiki, Rufaida Dhuhai; Kjeldsen, Shannon R.; Afzal, Hasifa; Al Hinai, Manal Saif; Zenger, Kyall R.; Jerry, Dean R.; Al-Abri, Mohammed Ali; Delghandi, Madjid (BMC genomics, 2018)
The scalloped spiny lobster (Panulirus homarus) is a popular seafood commodity worldwide and an important export item from Oman. Annual catches in commercial fisheries are in serious decline, which has resulted in calls for the development of an integrated stock management approach. In Oman, the scalloped spiny lobster is currently treated as a single management unit (MU) or stock and there is an absence of information on the genetic population structure of the species that can inform management decisions, particularly at a fine-scale level. This work is the first to identify genome-wide single nucleotide polymorphisms (SNPs) for P. homarus using Diversity Arrays Technology sequencing (DArT-seq) and to elucidate any stock structure in the species. After stringent filtering, 7988 high utility SNPs were discovered and used to assess the genetic diversity, connectivity and structure of P. homarus populations from Al Ashkharah, Masirah Island, Duqm, Ras Madrakah, Haitam, Ashuwaymiyah, Mirbat and Dhalkut landing sites. Pairwise F estimates revealed low differentiation among populations (pairwise F range = - 0.0008 - 0.0021). Analysis of genetic variation using putatively directional F outliers (504 SNPs) revealed higher and significant pairwise differentiation (p < 0.01) for all locations, with Ashuwaymiyah being the most diverged population (Ashuwaymiyah pairwise F range = 0.0288-0.0736). Analysis of population structure using Discriminant Analysis of Principal Components (DAPC) revealed a broad admixture among P. homarus, however, Ashuwaymiyah stock appeared to be potentially under local adaptive pressures. Fine scale analysis using Netview R provided further support for the general admixture of P. homarus. Findings here suggested that stocks of P. homarus along the Omani coastline are admixed. Yet, fishery managers need to treat the lobster stock from Ashuwaymiyah with caution as it might be subject to local adaptive pressures. We emphasize further study with larger number of samples to confirm the genetic status of the Ashuwaymiyah stock. The approach utilised in this study has high transferability in conservation and management of other marine stocks with similar biological and ecological attributes.